2016
DOI: 10.4999/uhod.14474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Follow-up by Phone Interview and Anger Management Training Provided to Patients with Breast Cancer Undergoing Radiotherapy on Levels of Self-Esteem, Anger and Depression

Abstract: Although surgery, medical oncology and radiation oncology are of importance in the management of breast cancers, psychiatry and supporting care such as psych-oncology nursing have an important role in the breast cancer. The present study aimed to measure the effect of follow-up by phone interviews and anger management training provided to patients with breast cancer on the levels of, anger, self-esteem and depression. The present study was conducted as a randomized-controlled experimental study between Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Finally, 20 RCTs with a total of 2190 participants were included in this meta-analysis. 57,11–14,1830 The process of study selection is shown in Figure 1.
Figure 1.PRISMA flow diagram of study selection.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 20 RCTs with a total of 2190 participants were included in this meta-analysis. 57,11–14,1830 The process of study selection is shown in Figure 1.
Figure 1.PRISMA flow diagram of study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…The types of technology used for telehealth intervention were not consistent among included studies. Ten studies adopted internet-based interventions, 7,[12][13][14]18,[22][23][24]26,29 seven studies adopted telephonebased interventions, 5,11,[19][20][21]25,27 and three studies combined internet with telephone for interventions. 6,28,30 Also, there are various scales used for outcome measures, and the intervention duration ranged from 2 weeks to 24 months.…”
Section: Search Process Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…By considering that previous studies regarded the cut-off point as 65 22,28 and that the maximum possible score is 100, self-esteem can be suggested to decrease in patients with gynecological cancers, as suggested in previous studies on cancer patients 14 …”
Section: Resultsmentioning
confidence: 95%
“…Self-esteem is defined as the respect of a person for herself/himself because of self-value and confidence. The decreased self-esteem found in the cancer patients possesses a significant problem for these patients 14,15 . Individuals caring and recognizing their bodies are concerned in their health and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Self-esteem is defined as the respect of a person feel for herself/himself because of self-value and confidence. Cancer patients are characterized by low self-esteem, which is considered as a significant problem for these patients [7].…”
Section: Introductionmentioning
confidence: 99%